The impact of language attrition on language teaching: the dynamics of linguistic knowledge retention and maintenance in multilingualism - Felipe Flores Kupske (Ilha do Desterro)
Language attrition has become a vibrant theme as it has implications for theoretical linguistics, including, for example, the organization of linguistic information in the brain and language processing. Insights from this area also have impact on the study of second language (L2) development and can feed the area of language teaching. Once language attrition may be of value for the study of language retention and maintenance, it can contribute to language teaching with long lasting results, more effective planning and syllabus design. In this perspective, as studies exploring L2 attrition are still limited, this article provides a synthesis of research on the area. By drawing from the Dynamic Model of Multilingualism and from the Threshold Hypothesis, it also explores the implications L2 attrition research has for language teaching with a view to establishing more informed language practices and policies.